Ultrasound biomicroscopy analysis of ciliary muscle dynamics and its relation to intra-ocular pressure after phacoemulsification in dogs - Kim, Donghee; Park, Sang-Eun; Hwang, Jiyi; Kang, Nanyoung; Jung, Ji Seung; Park, Kyung-Mee (Frontiers in Veterinary Science, 2024)
Introduction This study investigates the relationship between ciliary muscle dynamics, thickness, and the regulation of intraocular pressure (IOP), focusing on the progression of cataracts and changes post-phacoemulsification. It explores how these factors impact canine ocular health, particularly in the context of cataract development and subsequent surgical intervention. Materials and Methods Data was collected using Ultrasound Biomicroscopy (UBM) from dogs at the Veterinary Medical Teaching Hospital of Chungbuk National University, Korea. The study involved 57 eyes from 35 dogs, categorized into five groups: 13 normal eyes, 14 with incipient cataracts, 12 with immature cataracts, 6 with mature cataracts, and 12 post-phacoemulsification. UBM measurements assessed various ciliary muscle parameters including ciliary body axial length (CBAXL), ciliary process-sclera angle (CPSA), longitudinal fibers of ciliary muscle thickness (Lf-CMT), and longitudinal and radial fibers of ciliary muscle thickness (LRf-CMT). Results Findings indicated a decrease in CBAXL and an increase in Lf-CMT as cataracts progressed in severity. Post-phacoemulsification, there was a notable increase in CBAXL and a decrease in CPSA, Lf-CMT, and LRf-CMT, compared to both cataractous and normal eyes. Regression analysis revealed a significant positive association between CBAXL and IOP, alongside a negative association between Lf-CMT and IOP. These findings suggest that variations in ciliary muscle dynamics and thickness, as influenced by cataract progression and phacoemulsification, have distinct impacts on intraocular pressure. Discussion The study proposes that phacoemulsification leads to ciliary muscle contraction, causing an inward and anterior movement of the ciliary muscle. This movement results in the narrowing of the ciliary cleft and constriction of the unconventional outflow pathway, potentially causing an increased risk of glaucoma post-surgery. Our research contributes to understanding the anatomical and physiological changes in the canine eye following cataract surgery and underscores the importance of monitoring IOP and ciliary muscle dynamics in these patients.